Prevalence of maternal antenatal anxiety and its association with demographic and socioeconomic factors: A multicentre study in Italy - Cena, L. (Eur Psychiatry, 2020)
BACKGROUND. Maternal antenatal anxiety is very common, and despite its short- and long-term effects on both mothers and fetus outcomes, it has received less attention than it deserves in scientific research and clinical practice. Therefore, we aimed to estimate the prevalence of state anxiety in the antenatal period, and to analyze its association with demographic and socioeconomic factors. METHODS. A total of 1142 pregnant women from nine Italian healthcare centers were assessed through the state scale of the State–Trait Anxiety Inventory and a clinical interview. Demographic and socioeconomic factors were also measured. RESULTS. The prevalence of anxiety was 24.3% among pregnant women. There was a significantly higher risk of anxiety in pregnant women with low level of education (p < 0.01), who are jobless (p < 0.01), and who have economic problems (p < 0.01). Furthermore, pregnant women experience higher level of anxiety when they have not planned the pregnancy (p < 0.01), have a history of abortion (p < 0.05), and have children living at the time of the current pregnancy (p < 0.05). CONCLUSION. There exists a significant association between maternal antenatal anxiety and economic conditions. Early evaluation of socioeconomic status of pregnant women and their families in order to identify disadvantaged situations might reduce the prevalence of antenatal anxiety and its direct and indirect costs.